Alcohol use and the gender-specific risk of suicidal behavior: a systematic review and meta-analysis protocol - Lange, Shannon; Roerecke, Michael; Orpana, Heather; Bagge, Courtney; Rehm, Jürgen (Université d'Ottawa | University of Ottawa, 2022)
Abstract Background Alcohol use is an important risk factor for suicidal behavior, with a heightened risk found among women. The objective of this study is to determine the gender-specific risk of suicidal behaviors (suicide attempt and death by suicide) for different levels and dimensions of alcohol use—i.e., for (1) average alcohol volume consumed, (2) binge drinking, and (3) individuals with an alcohol use disorder. Methods We will systematically search the available literature for primary studies on the risk relationships specified above. Using a predetermined set of keywords, a comprehensive systematic literature search will be conducted in the following electronic databases: Embase, PsycINFO, PubMed, and Web of Science. The basic inclusion criteria will be (1) an original, quantitative (cohort, case–control or cross-sectional) study; with (2) a measure of risk of at least one dimension of our alcohol exposures in relation to at least one of our outcomes of interest (suicide attempt or death by suicide), and its corresponding measure of variability is reported (or sufficient data to calculate these); and (3) estimates of risk stratified by gender. Studies (1) that use only qualitative labels of alcohol use, and (2) where suicide attempt and non-suicidal self-harm cannot be disaggregated will be excluded. There will be no restrictions on language, geographical region, or year of publication. Two reviewers will independently perform the search and systematic assessment of each identified study and subsequent extraction of data. Categorical random-effects meta-analyses will be conducted to obtain gender-specific pooled risk estimates. Risk of bias will be assessed using the Risk of Bias In Non-randomised Studies—of Interventions tool and the Grading of Recommendations Assessment, Development and Evaluation approach will be used to rate the quality of evidence. Discussion This study will synthesize all available data on the gender-specific relationship between various dimensions of alcohol use and suicidal behavior simultaneously in a coherent framework. We will provide risk estimates with the detail needed to better understand the respective risk relationships and appreciate the burden of alcohol-attributable suicide. Systematic review registration PROSPERO CRD42022320918.